Design of highly efficient functionalized graphene-supported Pt based catalyst for PEM fuel cells - Liew, Zhi Hao. (2013)
Sustainable development which favours renewable energy sources over traditional energy source is the trend industries around the world are adopting. This trend is seen by many scientists and engineers as a long term goal in development due to the technical challenges at improving energy efficiencies of renewable energy resource like wind, tidal, solar power and fuel cells. When energy efficiencies are brought up, the cost of generating power of such resources could be brought down thereby encouraging commercialization of such energy resource[1] .